2019
DOI: 10.3390/su11215920
|View full text |Cite
|
Sign up to set email alerts
|

Regional Heterogeneity of Migrant Rent Affordability Stress in Urban China: A Comparison between Skilled and Unskilled Migrants at Prefecture Level and Above

Abstract: Rental housing unaffordability has been widely used to assess the housing poverty problem among immigrants in the developed and developing countries. China is experiencing an unprecedented urbanization process, with two-thirds of its 250 million migrants now being sheltered in private rental housing in the host cities. In this paper, we aimed to examine the rental housing unaffordability problems faced by migrant workers in urban China and provide policy recommendations for a more accessible and affordable mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 108 publications
0
3
0
Order By: Relevance
“…Research showed that rental housing unaffordability is one of the significant causes for mental distress among immigrants. [25] NYC has one of the highest rental rates in the world. [26] These international students, who mostly live on the financial support from the family back home, are struggling with the high rental cost in the City.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research showed that rental housing unaffordability is one of the significant causes for mental distress among immigrants. [25] NYC has one of the highest rental rates in the world. [26] These international students, who mostly live on the financial support from the family back home, are struggling with the high rental cost in the City.…”
Section: Discussionmentioning
confidence: 99%
“…Among these 20 students, there are 8 males and 12 females. These students (aged [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] have been in the USA from 7 years to less than 4 months. Demographics of these students are provided in Table A1.…”
mentioning
confidence: 99%
“…Scholars studying urban competitiveness have found that a larger pool of human capital leads to a higher technological capability, promotes innovation, fosters economic upgrading and encourages the development of technology clusters. Furthermore, the presence of high-skilled people has been found to create capital markets and enhance economic efficiency (Li et al 2019), which boosts economic development and adoption of international norms (Porter 1990;Zweig 2005;Welch and Hao 2015;Hao et al 2016;Zweig and Yang 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Food insecurity (with or without hunger) occurs in disadvantaged urban areas where culturally and linguistically diverse (CALD) communities and/or low income populations are concentrated [7,13]. Migrant families tend to congregate where possible, the location often dictated by affordability [14,15]. Such proximity also increases their ability to maintain family ties and culture, to enjoy the society of people from similar background and sharing a language, and to obtain easier access to culturally suitable foods [16].…”
Section: Introductionmentioning
confidence: 99%